An Intra-Site Spatial Analysis of Selected Faunal Remains from the Aztalan Site (47JE01) - (:unkn) unknown (My University, 2014)
Aztalan is one of the northern-most Mississippian villages east of the Mississippi River. It can be considered a multi-cultural settlement, having been occupied at the same time by both Mississippian and Late Woodland cultural groups. Because of this mixing of cultures, it offers unique insights on Woodland to Mississippian transitions in the Midwest. Many excavations over the years have led to a site-wide artifact assemblage scattered among different institutions. Much of the information available is of a site-wide provenience. Faunal remains are one line of evidence about life in the past. Intra-site analysis of faunal remains can shed light on variation in animal use within a community. Samuel Barrett was the first to conduct professional, systematic excavations at Aztalan (1933). His collection is housed at the Milwaukee Public Museum and includes extensive faunal remains. These are traceable to features located in the site's main habitation area. Using this feature-level provenience information, the faunal remains are compared between 30 features representing two separate areas of the site to address questions regarding spatial differences and possible human behaviors causing these differences.
Keywords: Aztalan; Faunal Analysis; Midwest Archaeology; Samuel Barrett; Spatial Analysis